Politik Hukum: Mencari Sejumlah Penjelasan - Syahriza Alkohir Anggoro (University of Merdeka Malang, 2019)
The emergence of the field of legal political studies has triggered a new understanding in seeing the law as a product of political power resulting from the process of negotiation and contestation of interests that work through the process of establishing law. Through a historical and theoretical search of the field of the study of legal politics, this article explores the emergence of the concept of legal politics and links it to the intellectual debate behind it. This research uses a short type of invitations (Statute Management of the Poor) to study the fairness of people who are less capable of dealing with justice. This article argues that the rise of “legal politics” studies in the 1990s cannot be separated from the authoritarian political context and background of the New Order which increasingly demonstrates the instrumentalist function of law as a means of maintaining the political power / interests of the regime and the emergence of theoretical needs in the academic world of legal science to theories that represent coherent legal analysis with the social, political and economic context that affect a product of law.How to cite item: Anggoro, S. (2019). Politik Hukum: Mencari Sejumlah Penjelasan. Jurnal Cakrawala Hukum, 10(1), 77-86. doi:https://doi.org/10.26905/idjch.v10i1.2871